Crossflow flow and heat transfer characteristics across a cam-shaped tube bank: a numerical study (2022)
Tubes are commonly employed in heat exchangers for their ease of production and capacity to sustain high pressure. In this study, the heat and flow transfer behaviour of cam-shaped tube bank in staggered configuration at varying angles of attack 0° to 180° was numerically investigated. The study was carried out by solving the continuity, momentum, energy and realizable k-ε transport equations using the finite volume-based ANSYS Fluent solver. This was performed to acquire the friction factor and heat transfer characteristics in the air inlet velocity range of 9 to 15 m/s. The results showed that the cam-shaped tube bank at varying angles of attack provided enhanced heat transfer characteristics relative to the circular tube bank. Also, camshaped tube banks at angles of attack of 90° and 120° exhibited the maximum heat transfer with 33.9 and 32.1% increase in Nusselt number over the circular tubes. Their friction factor was higher by 183 and 140.7%, respectively. The cam-shaped tube banks generally exhibited higher performance than the circular tube bank. Tube banks at angles of attack of 150° and 180° demonstrated higher thermal-hydraulic performance by 167.6 and 284.3% than the circular tubes, respectively. However, the tube banks at angles 90° and 120° exhibited lesser performance by value of 52.6 and 45.1%.